MSMEs’ Growth Potential and Operational Constraints: Evidence from Lampung Province, Indonesia - Puspa Komala Dewi; Dimas Danil Addhiyah; Ida Juvita Sari; Annisa Nur Afifa; Lisa Fenbrianti (Universitas Muhammadiyah Enrekang, 2024)
This study examines the growth potential and operational constraints of Micro, Small, and Medium Enterprises (MSMEs) in Lampung Province, Indonesia. Using a mixed-methods approach, the research draws on 120 questionnaire surveys, 15 semi-structured interviews, and regional economic reports. MSMEs serve as a key driver of the regional economy, particularly in agriculture, food processing, and creative industries. However, their development is constrained by limited financial access, restricted market reach, inadequate infrastructure, and insufficient human resource capacity. Quantitative findings analysis through descriptive statistics highlights obstacles related to credit access and operational capacity, while thematic analysis of qualitative data points to institutional gaps, bureaucratic loan procedures, and insufficient support services. Despite these challenges, enterprises that participate in business development programs and cooperative associations tend to show stronger resilience and adaptability. Therefore, the study recommends a comprehensive policy framework emphasizing financial accessibility, infrastructure improvement, broader digital technology adoption, and coordinated institutional support to foster a more resilient MSME ecosystem in Lampung.